AVIATION ENGINES DIAGNOSTICS BY ESTIMATING THE METAL CONTAMINATION IN OILS - K. I. Gryadunov; A. N. Kozlov; M. L. Nemchikov; I. S. Mel’nikova (Научный вестник МГТУ ГА)
Current trends of civil aviation development show a significant increase in the number of aircraft with aircraft piston engines. The Ministry of Transport of the Russian Federation is preparing a draft order on amendments to the Federal aviation rules for the preparation and performance of flights in civil aviation (FAP-128), which stipulate for simplified procedures of paid excursion flights implementation for light and ultralight aircraft and helicopters. It is obvious that this circumstance will significantly affect the expansion of the fleet of these aircraft. Accordingly, the state of piston engines operating on aviation gasoline value questions are becoming increasingly relevant. The current problems of aviation engines diagnostics by metal contents in oils are observed in the article. Their bugs, possible ways of solving this problems and bugs, actual developments in this direction are shown. The application examples of early diagnostic methods using the automated diagnostic complex “Prisma” are shown. The oil samples taken from An-2 aircraft АШ-62ИР piston engine analyses results attract the most interest. They show that with proper training of personnel the valuable information coming from the oil samples can be a source of important conclusions not only in aircraft engines accessories and assemblies state value, but also others systems, and also conclusions about the quality of fuel and lubricants used. Estimating the residual life method of the engine at various stages of its operating time on the metal content in the oils and the procedure for oil selecting, allowing to obtain reliable results, are suggested.